Competition for pollination by the lesser short‐tailed bat and its influence on the flowering phenology of some New Zealand endemics. (8th July 2014) - Cummings, G.; Anderson, S.; Dennis, T.; Toth, C.; Parsons, S.
Abstract The lesser short‐tailed bat, Mystacina tuberculata, is the only native mammalian pollinator in New Zealand and the only fully temperate bat pollinator in the world. Although this unique status as a pollinator is well recognized, its reduced abundance and cryptic behaviour means little research has been undertaken to assess the contribution of the lesser short‐tailed bat (hereafter 'short‐tailed bat') to pollination in New Zealand. Accordingly, pollination by short‐tailed bats has been assumed to be comparatively inconsequential, and the potential impacts of the bat's widespread extirpation have been overlooked. The recent discovery that the short‐tailed bat is a major pollinator for at least some of the plants it visits emphasizes the importance of exploring this species' role as a pollinator. Here, our aim was to provide an assessment of the competition for short‐tailed bat pollination through study of the temporal variation of flowering. Bats were sampled for pollen, and phenology surveys were conducted simultaneously. We found that the amount and type of pollen carried by the bats varied temporally, with one pollen type dominating samples at any given time. The two plants most consistently observed in the pollen samples flowered sequentially with little temporal overlap, suggesting that their flowering phenology may be adapted to minimize competition for the pollination services of the short‐tailed bat.